2017
DOI: 10.11113/umran2017.4n1-1.207
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Evolution of Higher Education in Malaysia

Abstract: Education is a process that develops human abilities and attitudes. Higher education began expanding its reach after WWII due to the growing political awareness of its importance for a nation’s future prospects. This study focuses on how higher education impacted Malaysian graduates by reviewing the system’s development from 1957 to present day and even beyond to 2025. A qualitative approach is used, based mostly on books, journals and qualified papers. We identify how Malaysia’s system of higher education sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This is to ensure technology-enabled innovations to deliver and tailor education for all students by leveraging technology-enabled models to enable more personalised learning (Malaysia Education Blueprint 2015-2025for Higher Education, 2015. According to Zain et al (2017), over the years, the evolution of Malaysia's education system has rapidly transformed, with standards and better systems in place and the shift towards internationalisation brought about by globalization, as a regional hub for higher education.…”
Section: Digitalisation Of Educationmentioning
confidence: 99%
“…This is to ensure technology-enabled innovations to deliver and tailor education for all students by leveraging technology-enabled models to enable more personalised learning (Malaysia Education Blueprint 2015-2025for Higher Education, 2015. According to Zain et al (2017), over the years, the evolution of Malaysia's education system has rapidly transformed, with standards and better systems in place and the shift towards internationalisation brought about by globalization, as a regional hub for higher education.…”
Section: Digitalisation Of Educationmentioning
confidence: 99%
“…The tertiary education sector in Malaysia is going through tremendous transformation (Mohd Zain et al 2017;Grapragasem et al 2014;Sirat 2010). This can be observed in the growth of the gross enrolment ratio in higher education -from 2% in 1965 to 32% in 2005 and 38% in 2009 (Tham 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysian higher education has continued to evolve over the years (Mohd Zain et al 2017). The Malaysia Education Blueprint 2015-2025 (MoE 2015) aims to continue increasing the quality of education and improving the position of Malaysia's higher education system in the world rankings (Grapragasem et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2 Many PHEI in Malaysia incurred losses for years and are unable to access adequate capital. 3 A recent report revealed that 55% of Malaysia's PHEI incurred losses, and approximately 44% were financially insolvent. As a result, more than 5,800 academics are faced with an uncertain career outlook, and approximately 121,000 students are at risk of receiving poorquality education.…”
Section: Introductionmentioning
confidence: 99%